Efektivitas Penggunaan Media Pembelajaran Sparkol Videoscribe Untuk Meningkatkan Penguasaan Materi Isim Isyarah Bagi Siswa Sdit Darul Istiqomah Kota Palangka Raya - Sundari, Yulviera; Ahmadi, Ahmadi (Institut Agama ISlam Negeri Palangka Raya, 2023)
The research is a quantitative study which aims to measure the effectiveness of using Sparkol Videoscribe media to improve mastery of Isim Isyarah material for class IV students at SDIT Darul Istiqomah, Palangka Raya City. The type of research used is an experiment with a one group pre-test post-test design model, while the data collection technique used is a test. The subject of this research is class IV which consists of 20 students. The results obtained showed that there was quite a significant increase in the average pre-test score (52.11) and post-test score (84.47), which showed an increase in results. Furthermore, from the results of the paired sample T-test, the sig value is known. 0,000. Based on the decision making rules in the paired sample T-test that the sig. value <0.05 or 0.000 <0.05, then the hypothesis H0 is rejected and for Ha it is accepted because there is a fairly large difference between the pre-test and post-test results. So, it can be concluded that the use of Sparkol Videoscribe learning media is effective in improving mastery of Isim Isyarah material for SDIT Darul Istiqomah Palangka Raya students